Rethinking Gold, Glory, and Gospel: An Interconnected Model of Colonial Power in Missionary Activity in North Sumatra, Indonesia - Khairani, Vira; Fitriani (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
This study reexamines the concepts of Gold, Glory, and Gospel by proposing an interconnected model of colonial power relations. While these concepts are commonly treated as separate motives of European expansion, this study argues that they operated simultaneously through the alignment of economic restructuring, political authority, and religious institutions. The analysis is grounded in a qualitative approach based on historical sociology, using a critical reading of historiographical sources related to the activities of the Rheinische Missionsgesellschaft (RMG) in Batak regions of North Sumatra between 1860 and 1910. The findings indicate that missionary institutions were embedded within broader colonial structures. Educational initiatives contributed to the formation of a local administrative workforce, missionary knowledge production supported colonial governance, and religious practices facilitated cultural adaptation that reshaped local belief systems. These processes were interconnected and functioned within a broader configuration of power that extended beyond military and economic control. The study further shows that the interaction between economic, political, and religious processes formed a structured and mutually reinforcing system. This configuration shows how colonial expansion operated through institutional and cultural mechanisms that were sustained over time.